Deskripsi Kualitatif Masalah Perawat dalam Melakukan Auskultasi di Ruang Perawatan Intensive Care Unit - Ricky Prawira; Suhartini Ismail; Andrew Johan; Rifky Ismail (Jurnal Keperawatan Silampari, 2023)
This study aims to analyze the problems of nurses in conducting auscultation in the intensive care unit. The research method used is descriptive qualitative research. The results of the study found three main themes found in this study, including 1) the time used for auscultation was minimal due to the large number of nurses' tasks to be completed, 2) the stethoscope used should have a clear sound when used, 3) the stethoscope should be more flexible in shape so that it is accessible to in use. In conclusion, the problem nurses face in conducting auscultation examinations on critical patients is the need for a stethoscope that has a more precise sound output and is flexible in its use. Keywords: Auscultation, Intensive Care Unit, Stethoscope